Ciclos políticos nas funções orçamentárias dos municípios brasileiros: uma análise para o período 1990 - 2005 via dados em painel - Sakurai, Sergio Naruhiko (Estudos Econômicos (São Paulo), 2009)
The main purpose of the present study is an investigation concerning the possibility of electoral and partisan cycles in the budgetary functions of Brazilian cities over the 1990 - 2005 period. For the first phenomenon, the econometric results provide evidence that health and sanitation, housing and urbanism, social assistance & retirement system and transports are the most susceptible functions to changes in election years. With reference to the partisan cycles, the influence of partisanship heterogeneity on the municipal expenditures is furthermore suggested by the outcomes. Finally, we have found indication of an expenditure composition effect over the time, also influenced by the Brazilian Law of Fiscal Responsibility.